USE IN THE PEOPLE’S ECONOMY OF PLANTS OF THE CATEGORY OF AILANTA AND GRAPE AND THEIR MEDICINAL PROPERTIES - Khamdam, Tursunov; Ibragimovich, Yusupov Ilhamdjan (The journal of contemporary issues in business and government, 2022)
The article describes in detail the experiments on the joint cultivation of ailant and grapes, experiments on the creation of new varieties, agricultural technologies for the cultivation of environmentally friendly products, their use in industry, food and scientific medicine in the Republic.